Rab GTPases, tethers, and SNAREs work together to regulate Arabidopsis cell plate formation - Shi, Yumei; Luo, Changxin; Xiang, Yun; Qian, Dong (Frontiers in Plant Science, 2023)
Cell plates are transient structures formed by the fusion of vesicles at the center of the dividing plane; furthermore, these are precursors to new cell walls and are essential for cytokinesis. Cell plate formation requires a highly coordinated process of cytoskeletal rearrangement, vesicle accumulation and fusion, and membrane maturation. Tethering factors have been shown to interact with the Ras superfamily of small GTP binding proteins (Rab GTPases) and soluble N-ethylmaleimide-sensitive factor attachment protein receptors (SNAREs), which are essential for cell plate formation during cytokinesis and are fundamental for maintaining normal plant growth and development. In Arabidopsis thaliana, members of the Rab GTPases, tethers, and SNAREs are localized in cell plates, and mutations in the genes encoding these proteins result in typical cytokinesis-defective phenotypes, such as the formation of abnormal cell plates, multinucleated cells, and incomplete cell walls. This review highlights recent findings on vesicle trafficking during cell plate formation mediated by Rab GTPases, tethers, and SNAREs.